Faking Good Among Porn-Addicted Adolescents - Dian Fairuz Izdihar; Fikry Ravi Fauzi; Diah Ayu Aguspa Dita; Miskatyas Putri Aransih; Pukovisa Prawiroharjo; Elly Risman; Rizki Edmi Edison (International Conference of Mental Health, Neuroscience, and Cyber-psychology)
Pornography content is becoming an increasingly serious problem in Indonesia, where it is suspected that around 97% of 1,600 children and adolescents have been exposed to pornography. Various efforts have been made by the government to minimize the prevalence of pornography content, such as by blocking porn-suspected sites. It is also known that the exposure of massive and periodic pornography content to children and adolescents can result in adverse effects in the form of addiction. Research results with EEG (Edison, RE., et al) and fMRI (Prawiroharjo, P., et al) have reported changes in the brain activity of children and adolescents who were suspected as having addiction to pornography content. Interestingly, there is a tendency to a phenomenon of faking good among the subjects. This article discusses the phenomenon from the perspectives of psychology and neuroscience.